Factors influencing acceptability of voluntary HIV testing among pregnant women in Gamboma, Republic of Congo. (December 2015) - Ghoma-Linguissi, Laure; Ebourombi, Dagene; Sidibe, Anissa; Kivouele, Thomas; Vouvoungui, Jeannhey; Poulain, Pierre; Ntoumi, Francine
Abstract Background This study was carried out to identify factors affecting the acceptability of voluntary HIV testing among pregnant women in a semi-rural city, Gamboma, Republic of Congo. Methods A cross-sectional study was conducted between January and September 2012. Pregnant women attending antenatal heath care at an integrated health center were enrolled after informed consent and followed through voluntary HIV testing. Results Among 136 participants, 98 women (72 %) accepted voluntary HIV testing after pre-test counseling. Women with basic education, those who cited blood transfusion as a mode of transmission and prevention of mother-to-child transmission (MTCT) were more likely to accept testing as well those informed about free HIV testing. Interestingly, pregnant women who had heard about HIV/AIDS from hospital setting were less likely to accept testing. Conclusions Our data indicate that increasing general education on HIV transmission/prevention modes is crucial for increasing acceptability of screening. Furthermore, HIV/AIDS knowledge disseminated to patients in hospital settings should be carefully monitored. Lastly, scaling-up MTCT services along with a better and larger community information, may address accessibility barriers observed in the present study.